Oh, bother! Someone won$1 (Bt share s - Birney, Betty; Milne, A. A. (Alan Alexander), 1882-1956.; Atelier Philippe Harchy (New York : Golden Book [Milwaukee, Wis.] : Penworthy [distributor], 1993)
On a hot day, Pooh, Piglet, Eeyore and Owl search for the perfect log to ride downstream in the Hundred Acre Woods, but Rabbit, who has found one, is reluctant to share.
At head of title: Disney.
"Based on the $1 (BWinnie the Pooh works by A.A. Milne and E.H. Shepard."s
Keywords: Sharing -- Juvenile fiction; Animals -- Juvenile fiction; Winnie-the-Pooh (Fictitious character) -- Juvenile fiction; Rabbits -- Juvenile fiction; Sharing -- Fiction; Animals -- Fiction; Winnie-the-Pooh (Fictitious character) -- Fiction; Rabbits -- Fiction